ELF-MF and Childhood Leukimia in Observational Studies and Meta Analysis (1999-2025): A Narrative Literature Review - Jose A. Martinez (Journal of Community Medicine and Public Health Research, 2026)
Extremely low-frequency magnetic fields (ELF-MF) have been investigated for several decades as a potential risk factor for childhood leukemia, generating a substantial body of observational studies and meta-analyses with heterogeneous findings. This narrative review provides a chronological and methodological synthesis of epidemiological evidence published between 1999 and 2025. We focus specifically on how different exposure assessment strategies have influenced reported risk estimates over time. Early pooled analyses and case–control studies consistently reported increased leukemia risks at average residential exposure levels above 0.3–0.4 μT, largely based on proxy measures such as distance to high-voltage power lines or simplified field calculations. However, more recent large-scale studies incorporating refined exposure assessment -including long-term measurements and three-dimensional modeling of overhead and underground conductors- have generally yielded weaker, inconsistent, or null associations when risk is analyzed as a function of estimated magnetic field intensity. Notably, some excess risks based on residential proximity persist, especially among younger children, highlighting a growing divergence between distance-based and field-based metrics. This pattern suggests that exposure misclassification, residual confounding, or correlated infrastructural factors may partly account for earlier positive findings. Overall, the reviewed evidence supports the continued classification of ELF-MF as a possible carcinogen while underscoring the need for improved exposure characterization to clarify causal inference and inform proportionate public health policies.